Dystocia Due to Ringwomb in Corriedale Ewe at an Organized Farm in Kashmir - Ahmad Malik, Asloob; Qayoom Mir, Abdul; Yousuf, Nahida; Ahmad Malik, Fasal (The Indian Journal of Animal Reproduction, 2025)
The present case report explains a case of dystocia due to Ringwomb in a Corriedale ewe and its successful management  at an organized sheep and goat farm in Kashmir valley. The animal had history of recurrent vaginal prolapse and was  managed with standard treatment including applying Buhner’s sutures. One month later the animal started showing  signs of lambing and straining but was unable to expel the fetus. On per vaginal examination the cervix was minimally  dilated with only three fingers able to pass and the head of the fetus was near the internal os of cervix. The animal was  treated with single shot of Dexamethasone (2ml) and Inj. Epidosin (3ml) q.6.h. On next day cervix was fully dilated and  the fetal head was palpated. The emphysema had already set in, that made the extraction difficult. However, following  mutation the male lamb was delivered by partial traction. The ewe was treated with antibiotics, anti-inflammatory drugs,  antihistaminic, intrauterine antibiotics and IV fluids. The ewe had an uneventful recovery thereafter
Keywords: Ewe; Kashmir; Organized farm; Ringwomb